Reference electrode, preparation method thereof and battery

By using a combination of modified alkali metal particles and nonwoven fabrics in the reference electrode, the shortcomings of existing reference electrodes in monitoring accuracy and service life are solved, and the electrochemical properties of high precision and long life are achieved.

CN119481391APending Publication Date: 2025-02-18BYD CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411465157.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing reference electrodes have shortcomings in monitoring accuracy and service life. The high chemical activity of metal lithium leads to short service life, while the lithium iron phosphate electrode sheet and lithium titanate electrode sheet have low lithium content and weak signal. Monitoring Poor accuracy.

Method used

Modified alkali metal particles are used, where the alkali metal core is metal lithium, covered with a passivation layer, combined with non-woven fabric to provide support framework and pores, adding ion migration channels and monitoring area.

Benefits of technology

It improves the monitoring accuracy and electrochemical stability of the reference electrode, extends the service life, and has both high precision and long life performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481391A_ABST
    Figure CN119481391A_ABST
Patent Text Reader

Abstract

The invention provides a reference electrode, a preparation method thereof and a battery, the reference electrode comprises a non-woven fabric and modified alkali metal particles loaded on the non-woven fabric, and the modified alkali metal particles comprise an alkali metal core and a passivation layer coating at least part of the surface of the alkali metal core. The alkali metal inner core of the modified alkali metal particles in the reference electrode improves the accuracy and sensitivity of the reference electrode, and the passivation layer coating at least part of the surface of the alkali metal inner core improves the electrochemical stability of the reference electrode, so that the reference electrode has good precision and longer service life; and the non-woven fabric provides a supporting framework and pores for the reference electrode, so that ion migration channels are increased, and the monitoring area of the reference electrode is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the field of reference electrode technology, and in particular to a reference electrode, a preparation method thereof, and a battery. Background Art

[0002] With the widespread application of lithium-ion batteries in various fields such as energy storage and electronic devices, the requirements for lithium-ion battery performance are becoming higher and higher. By analyzing and monitoring the battery, the battery performance can be improved in a targeted manner. At present, a reference electrode is usually set in the battery, and a three-electrode system is used to monitor the potential and impedance of the battery charging and discharging process, so as to improve the battery performance in a targeted manner. Currently, the commonly used reference electrodes are mainly metallic lithium, lithium iron phosphate pole pieces, lithium titanate pole pieces, etc. Among them, metallic lithium has a high chemical activity and is very easy to react with the electrolyte, reducing the service life of the reference electrode; lithium iron phosphate pole pieces and lithium titanate pole pieces have the problems of low lithium content, weak signals, and poor monitoring accuracy. Summary of the invention

[0003] In view of this, the present application provides a reference electrode, a preparation method thereof and a battery, in which the alkali metal core of the modified alkali metal particles in the reference electrode improves the accuracy and sensitivity of the reference electrode, and the passivation layer coated on at least part of the surface of the alkali metal core improves the electrochemical stability of the reference electrode, so that the reference electrode has both good precision and a long service life, and the non-woven fabric provides a supporting skeleton and pores for the reference electrode, thereby increasing the channels for ion migration and the monitoring area of ​​the reference electrode.

[0004] In a first aspect, the present application provides a reference electrode, which includes a non-woven fabric and modified alkali metal particles loaded on the non-woven fabric, wherein the modified alkali metal particles include an alkali metal core and a passivation layer coated on at least a portion of the surface of the alkali metal core.

[0005] In the embodiment of the present application, the non-woven fabric has a porous hole structure, and at least part of the modified alkali metal particles are contained in the porous holes.

[0006] In the embodiment of the present application, the pore size of the porous holes is 0.01 μm-5 μm.

[0007] In an embodiment of the present application, the non-woven fabric includes a plurality of non-woven fiber filaments, at least some of which are interwoven with each other, and at least some of the non-woven fiber filaments include a non-woven fiber filament matrix and a conductive polymer coating layer coated on the surface of the non-woven fiber filament matrix.

[0008] In the embodiment of the present application, the diameter of the non-woven fiber matrix is ​​0.5 μm-5 μm; the thickness of the conductive polymer coating layer is 0.1 μm-2 μm.

[0009] In the embodiment of the present application, the specific surface area of ​​the nonwoven fabric is 0.5 m 2 / g-1.6m 2 / g.

[0010] In an embodiment of the present application, the material in the conductive polymer coating layer includes at least one of polyaniline, polypyrrole and polyacetylene.

[0011] In the embodiment of the present application, the particle size D50 of the alkali metal core is 0.05 μm-10 μm.

[0012] In the embodiment of the present application, it is characterized in that the alkali metal core is metallic lithium.

[0013] In the implementation manner of the present application, the thickness of the passivation layer is 1nm-100nm.

[0014] In an embodiment of the present application, the passivation layer is a SEI film coating layer, and the SEI film coating layer includes an inorganic lithium salt; the inorganic lithium salt includes at least one of LiF, Li2SO3, Li2SO4, LiN, Li3PO4, Li2CO3, Li2O, Li2O2, LiPF and LiPOF.

[0015] In the embodiment of the present application, the mass percentage of the modified alkali metal particles in the reference electrode is 10%-80%.

[0016] In the embodiment of the present application, the thickness of the reference electrode is 1 μm-20 μm; the specific surface area of ​​the reference electrode is 0.6 m 2 / g-1.8m 2 / g; the porosity of the reference electrode is 20%-60%; the compaction density of the reference electrode is 1.5g / cm 3 -2.8g / cm 3 .

[0017] The second aspect of the present application provides a method for preparing the reference electrode provided in the first aspect, comprising:

[0018] placing alkali metal particles in a passivation solution to obtain modified alkali metal particles;

[0019] The modified alkali metal particles are pressed and compounded with non-woven fabric to obtain a reference electrode.

[0020] In an embodiment of the present application, the passivation solution includes a lithium salt and a solvent; the lithium salt includes at least one of LiPF6, LiClO4, LiFSI and LiTFSI; the solvent includes a carbonate solvent, and the carbonate solvent includes at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.

[0021] In the embodiment of the present application, the non-woven fabric is further modified by coating with a conductive polymer before the pressing and compounding; the polymer comprises at least one of polyaniline, polypyrrole and polyacetylene.

[0022] The third aspect of the present application provides a battery, which includes a positive electrode, a diaphragm, a reference electrode, a diaphragm, a negative electrode stacked in sequence, and an electrolyte located between the positive electrode and the negative electrode, and the reference electrode includes the reference electrode provided in the first aspect or the reference electrode prepared by the preparation method provided in the second aspect.

[0023] A fourth aspect of the present application provides an electrical device, which includes the battery provided in the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A schematic diagram of the cross-sectional structure of a reference electrode provided in an embodiment of the present application;

[0025] Figure 2 A schematic diagram of the cross-sectional structure of modified alkali metal particles in the reference electrode provided in an embodiment of the present application;

[0026] Figure 3 A schematic diagram of the radial cross-sectional structure of non-woven fiber filaments provided in an embodiment of the present application;

[0027] Figure 4 A flow chart of a method for preparing a reference electrode provided in an embodiment of the present application.

[0028] Description of Figure Numbers

[0029] 10-reference electrode; 11-nonwoven fabric; 12-modified alkali metal particles; 110-nonwoven fabric fiber; 1101-nonwoven fabric fiber matrix; 1102-conductive polymer coating layer; 121-alkali metal core; 122-passivation layer. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with preferred embodiments, but the protection scope of the present application is not limited to the following specific embodiments.

[0031] In the present application, all professional terms have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present application.

[0032] With the widespread application of lithium-ion batteries in various fields such as energy storage and electronic devices, the requirements for lithium-ion battery performance are becoming higher and higher. By analyzing and monitoring the battery, the battery performance can be improved in a targeted manner. At present, a reference electrode is usually set in the battery, and a three-electrode system is used to monitor the potential and impedance of the battery charging and discharging process, so as to improve the battery performance in a targeted manner. At present, the commonly used reference electrodes are mainly metallic lithium and pole-type reference electrodes such as lithium iron phosphate pole pieces and lithium titanate pole pieces. Among them, metallic lithium has good accuracy and sensitivity in the monitoring process, but its chemical activity is high and its stability is poor. It is very easy to have side reactions with the electrolyte, which reduces the service life of the reference electrode; although lithium iron phosphate pole pieces and lithium titanate pole pieces have high electrochemical stability, they contain less lithium, have weak signals, and have poor monitoring accuracy.

[0033] In order to make the reference electrode have good monitoring accuracy and service life, there are usually the following methods to modify the reference electrode: coating the metal lithium with polymer or solid electrolyte, using molten lithium or increasing the pre-embedded length of the lithium-plated copper wire electrode to phase-update the consumed three electrodes. However, the coating of metal lithium still has the problem of difficult control of coating thickness and difficulty in inhibiting side reactions with the electrolyte; the preparation of molten lithium involves a high-temperature lithium melting process, which is relatively dangerous; copper wire pulling can also easily lead to the distribution of metal lithium on the copper wire being thin on the top and thick on the bottom, and the pre-embedded copper wire increases the complexity of the battery cell structure and is not very practical. In addition, the monitoring area of ​​a single copper wire is limited, resulting in a decrease in the accuracy of reference electrode monitoring.

[0034] In response to the above problems, the present application provides a reference electrode, in which the alkali metal core of the modified alkali metal particles improves the accuracy and sensitivity of the reference electrode, and the passivation layer coated on the surface of the alkali metal core improves the electrochemical stability of the reference electrode, so that the reference electrode has both good precision and a long service life, and the non-woven fabric provides a supporting skeleton and pores for the reference electrode, increasing the channel for ion migration and the monitoring area of ​​the reference electrode.

[0035] See also Figure 1, an embodiment of the present application provides a reference electrode 10, and the reference electrode 10 includes a non-woven fabric 11 and modified alkali metal particles 12 loaded on the non-woven fabric 11. The non-woven fabric 11 in the reference electrode 10 provided in the present application plays the role of providing a supporting skeleton and pores. The pore structure in the non-woven fabric can absorb electrolyte to provide a medium and channel for ion migration, and the non-woven fabric formed by interweaving fiber filaments increases the monitoring area of ​​the reference electrode, which allows the reference electrode to monitor and analyze more areas, thereby improving the sensitivity and accuracy of the reference electrode monitoring. The modified alkali metal particles 12 in the reference electrode 10 have both good monitoring accuracy and a long service life. Combining them with the non-woven fabric 11 can obtain a reference electrode with both high accuracy and long service life. In the embodiment of the present application, a schematic diagram of the cross-sectional structure of the modified alkali metal particles 12 in the reference electrode 10 is shown in FIG. Figure 2 As shown, the modified alkali metal particles 12 include an alkali metal core 121 and a passivation layer 122 coated on at least part of the surface of the alkali metal core 121. In the embodiment of the present application, the passivation layer 122 is obtained by the reaction of the alkali metal and the passivation solution. The present application simulates the first charge and discharge process of the liquid battery by directly reacting the alkali metal with the passivation solution, and the electrode material and the electrolyte react at the solid-liquid interface to form a passivation layer covering the surface of the electrode material, that is, SEI (Solid Electrolyte Interface membrane, solid electrolyte interface) membrane. In some embodiments, the passivation includes a lithium salt and a solvent, and the lithium salt includes at least one of LiPF6, LiClO4, LiFSI and LiTFSI; the solvent includes a carbonate solvent, and the carbonate solvent includes at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and methyl ethyl carbonate.

[0036] The alkali metal kernel in the modified alkali metal particles provided by the present application has good kinetic properties, a large exchange current density and good reversibility, so that the reference electrode can quickly return to the equilibrium state even if a current passes through it, and polarization is not easy to occur, thereby making the reference electrode have a higher measurement accuracy. At the same time, the alkali metal kernel has a high activity and is easy to react with the electrolyte. Therefore, the present application coats the surface of the alkali metal kernel with a passivation layer with low activity. The uniform and dense passivation layer can effectively isolate the alkali metal kernel from direct contact with the electrolyte and cause side reactions, thereby keeping the electrode potential of the reference electrode stable and improving the stability of the reference electrode. In addition, the passivation layer can also effectively prevent the lithium-ion battery from reacting with the dissolution of the positive / negative electrode during the cycle and then failing, thereby extending the service life of the reference electrode and meeting the life requirement of the reference electrode to achieve potential monitoring of the battery throughout its life cycle.

[0037] In the embodiment of the present application, the particle size D50 of the alkali metal kernel 121 is 0.05μm-10μm. In some specific embodiments of the present application, the particle size D50 of the alkali metal kernel 121 can be, for example, 0.05μm, 0.1μm, 0.2μm, 0.3μm, 0.5μm, 0.8μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm. Controlling the size of the alkali metal kernel within the above range can make the reference electrode have sufficient alkali metal content, effectively avoiding the problem of reduced monitoring accuracy caused by too low alkali metal content resulting in too weak signal of the reference electrode, and further improving the sensitivity and accuracy of reference electrode potential monitoring. In some specific embodiments of the present application, the alkali metal kernel is metallic lithium. In this application, the particle size D50 is specifically Dv50, which refers to the particle size corresponding to when the cumulative particle size distribution percentage of the measured sample reaches 50%. The physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. It can be measured using a laser particle size detector.

[0038] In the embodiment of the present application, the passivation layer 122 may completely or partially cover the alkali metal core 121. In some embodiments, the passivation layer 122 completely covers the alkali metal core 121. In the embodiment of the present application, the composition of the passivation layer can be regulated by selecting appropriate passivation liquid components, thereby obtaining a passivation layer that meets different performance requirements.

[0039] In the implementation manner of the present application, the thickness of the passivation layer 122 is 1nm-100nm. In some specific embodiments, the thickness of the passivation layer 122 can be, for example, 1nm, 2nm, 3nm, 5nm, 8nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm. The present application can further enhance the bonding force between the passivation layer and the alkali metal core by controlling the thickness of the passivation layer within a suitable range, thereby more effectively avoiding the fall-off of the passivation layer, and can also enhance the coating effect of the passivation layer on the alkali metal core, further enhancing the measurement accuracy and service life of the reference electrode.

[0040] In some embodiments of the present application, the passivation layer 122 is a SEI film coating layer, which is obtained by reacting an alkali metal with a passivation solution, and includes an inorganic lithium salt and an organic component. In some embodiments, the organic component includes but is not limited to alkyl lithium carbonate, alkoxy lithium, alkyl lithium sulfonate and lithium oligomers, and the inorganic lithium salt includes but is not limited to LiF, Li2SO3, Li2SO4, LiN, Li3PO4, Li2CO3, Li2O, Li2O2, LiPF and LiPOF.

[0041] In the implementation mode of this application, Figure 1As shown, the non-woven fabric 11 has a three-dimensional porous skeleton porous hole structure formed by interweaving a plurality of non-woven fabric fibers, and at least part of the modified alkali metal particles 12 are contained in the porous holes. In some embodiments of the present application, part of the modified alkali metal particles 12 are contained in the porous holes of the non-woven fabric 11, and part of the modified alkali metal particles 12 are attached to the surface of the non-woven fabric 11. The non-woven fabric 11 in the reference electrode 10 of the present application includes a three-dimensional porous skeleton formed by interweaving a plurality of non-woven fabric fibers. On the one hand, the three-dimensional porous skeleton can play a role in supporting the reference electrode. On the other hand, the three-dimensional porous skeleton provides a porous hole structure for the reference electrode. The porous holes can absorb electrolyte and prevent the reference electrode from hindering the conduction of lithium ions. The porous holes also provide a containing space for the modified alkali metal particles, so that the modified alkali metal particles are more evenly and effectively distributed in the reference electrode. In addition, the three-dimensional porous skeleton of the non-woven fabric 11 further increases the specific surface area of ​​the reference electrode, thereby increasing the effective monitoring area of ​​the reference electrode, allowing the reference electrode to monitor more areas of the battery, further improving the accuracy of reference electrode monitoring and reducing errors caused by too small a monitoring area.

[0042] In the implementation mode of the present application, the pore size of the porous holes is 0.01μm-5μm. In some specific embodiments of the present application, the pore size of the porous holes can be, for example, 0.01μm, 0.02μm, 0.05μm, 0.1μm, 0.2μm, 0.5μm, 1μm, 1.2μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm. The present application can adjust the porosity of the reference electrode by controlling the porous holes of the non-woven fabric within a suitable range, further promote the embedding of the modified alkali metal particles and control the pores of the reference electrode within a suitable range, so as to facilitate the immersion of the electrolyte.

[0043] like Figure 3 As shown, in the embodiment of the present application, the non-woven fabric 11 includes a plurality of non-woven fabric fiber filaments 110, at least some of the plurality of non-woven fabric fiber filaments 110 are interwoven to form a three-dimensional porous skeleton, and at least some of the non-woven fabric fiber filaments 110 include a non-woven fabric fiber filament matrix 1101 and a conductive polymer coating layer 1102 coated on the surface of the non-woven fabric fiber filament matrix 1101. In the embodiment of the present application, the coating of the non-woven fabric fiber filament matrix 1101 by the conductive polymer coating layer 1102 can be complete coating or partial coating. In some specific embodiments, the coating of the non-woven fabric fiber filament matrix 1101 by the conductive polymer coating layer 1102 is partial coating. By coating and modifying the non-woven fabric fiber filament matrix with a conductive polymer, the non-woven fabric can be provided with an electronic conductivity, thereby improving the electronic conductivity of the reference electrode.

[0044] In the embodiment of the present application, the diameter of the non-woven fiber matrix 1101 is 0.5μm-5μm; the thickness of the conductive polymer coating layer 1102 is 0.1μm-2μm. In some specific embodiments of the present application, the diameter of the non-woven fiber matrix 1101 can be, for example, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm; the thickness of the conductive polymer coating layer 1102 can be, for example, 0.1μm, 0.2μm, 0.5μm, 0.8μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm. The present application can further obtain a reference electrode with good support and conductivity by controlling the size of the non-woven fiber matrix and the thickness of the conductive polymer coating layer within the above-mentioned appropriate range.

[0045] In some embodiments of the present application, the conductive polymer coating layer 1102 has a porous structure, which can make the conductive polymer coating layer have the ability to absorb electrolyte, further improve the absorption and accommodation capacity of the reference electrode for the electrolyte, and provide more medium and channels for lithium ion migration. In the embodiment of the present application, the specific surface area of ​​the non-woven fabric 11 is 0.5m 2 / g-1.6m 2 In some specific embodiments, the specific surface area of ​​the nonwoven fabric 11 may be, for example, 0.5 m 2 / g. Controlling the specific surface area of ​​the nonwoven fabric 11 within the above range can further improve the conductivity and monitoring area of ​​the reference electrode. In the present application, the specific surface area can be obtained by using the BET specific surface area of ​​N2 adsorption and desorption test.

[0046] In the embodiment of the present application, the material of the non-woven fiber matrix 1101 is a non-woven material commonly used in the field, including but not limited to polyester fiber (PET). In the embodiment of the present application, the material in the conductive polymer coating layer includes at least one of polyaniline, polypyrrole and polyacetylene. In some specific embodiments, the material in the conductive polymer coating layer includes polyaniline. The non-woven fabric itself does not have conductivity. The present application can provide the non-woven fabric with good electrical conductivity by selecting a conductive polymer with excellent conductivity as the material of the conductive polymer coating layer, thereby further improving the potential monitoring area of ​​the reference electrode.

[0047] In an embodiment of the present application, the mass percentage of the modified alkali metal particles in the reference electrode is 10%-80%. In some specific embodiments, the mass percentage of the modified alkali metal particles in the reference electrode can be, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%. By controlling the content of the modified alkali metal particles in the reference electrode within the above range, the content of the alkali metal in the reference electrode can be further controlled, further improving the monitoring accuracy of the reference electrode. In the present application, the mass percentage of the modified alkali metal particles in the reference electrode can be measured by an inductively coupled plasma spectrometer (ICP).

[0048] In the embodiment of the present application, the thickness of the reference electrode ( Figure 1 h) is 1 μm-20 μm; the compaction density of the reference electrode is 1.5 g / cm 3 -2.8g / cm 3 In some specific embodiments of the present application, the thickness of the reference electrode can be, for example, 1 μm, 2 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 13 μm, 15 μm, 18 μm, or 20 μm; the compaction density of the reference electrode can be, for example, 1.5 g / cm 3 , 1.6g / cm 3 , 1.8g / cm 3 , 2g / cm 3 , 2.2g / cm 3 , 2.5g / cm 3 , 2.8g / cm 3 . The present application can further improve the compactness of the reference electrode and reduce the negative impact caused by its contact with the positive and negative electrode plates by controlling the thickness and density of the reference electrode within a suitable range, thereby further extending the service life of the reference electrode. In the present application, the mass of the reference electrode can be weighed using an analytical balance, the thickness of the reference electrode can be measured using a micrometer, the length and width of the reference electrode can be measured using a ruler, and the area of ​​the reference electrode can be calculated (the area of ​​the reference electrode = the length * width of the reference electrode), and the compaction density of the reference electrode = the mass of the reference electrode / (the thickness of the reference electrode * the area of ​​the reference electrode).

[0049] In the embodiment of the present application, the specific surface area of ​​the reference electrode is 0.6 m 2 / g-1.8m 2 / g; the porosity of the reference electrode is 20%-60%. In some embodiments of the present application, the specific surface area of ​​the reference electrode can be, for example, 0.6 m 2 / g, 0.8m 2 / g, 1m 2 / g, 1.2m2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.8m 2 / g; the porosity of the reference electrode can be, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%. The present application can further improve the permeability of the electrolyte in the reference electrode by controlling the specific surface area and porosity of the reference electrode within the above range, thereby avoiding the influence of the reference electrode on the lithium insertion of the negative electrode to a certain extent.

[0050] The present application provides a reference electrode having good precision and long life obtained by compounding alkali metal particles coated with a passivation film with a non-woven fabric, and the non-woven fabric provides a supporting skeleton and pores for the reference electrode, thereby increasing the channel for ion migration and the monitoring area of ​​the reference electrode.

[0051] The present application also provides a method for preparing the reference electrode provided above. Figure 4 The flowchart of the preparation method comprises:

[0052] S101, placing alkali metal particles into a passivation solution to obtain modified alkali metal particles;

[0053] S102, pressing and compounding the modified alkali metal particles and non-woven fabric to obtain a reference electrode.

[0054] In step S101, the passivation solution includes a lithium salt and a solvent. In an embodiment of the present application, the lithium salt includes at least one of LiPF6, LiClO4, LiFSI and LiTFSI. In some embodiments of the present application, the solvent includes a carbonate solvent. Compared with other solvents such as carboxylic acid ester solvents, ether solvents, etc., the present application uses carbonate solvents to further improve the film-forming stability of the reaction between the passivation solution and the alkali metal particles. In some specific embodiments, the carbonate solvent includes at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate. In the present application, carbonate solvents can be divided into linear carbonate solvents (such as dimethyl carbonate, diethyl carbonate) and cyclic carbonate solvents (such as ethylene carbonate, propylene carbonate), and in some specific implementations, the solvent includes at least one of linear carbonate solvents and at least one of cyclic carbonate solvents. Lithium salts have low solubility in linear carbonate solvents but good fluidity of linear carbonate solvents, while they have high solubility in cyclic carbonate solvents but high viscosity and poor fluidity of cyclic carbonate solvents, so the use of cyclic carbonate solvents and linear carbonate solvents can further improve the solubility of lithium salts in solvents while ensuring good fluidity of the solution. In an embodiment of the present application, the concentration of lithium salts in the electrolyte is 0.8mol / L-1.2mol / L. In some specific embodiments, the concentration of lithium salts in the electrolyte can be, for example, 0.8mol / L, 0.9mol / L, 1mol / L, 1.1mol / L, 0.2mol / L.

[0055] In the embodiment of the present application, the metal lithium is placed in the electrolyte and also includes a stirring treatment. In the embodiment of the present application, the stirring speed of the stirring treatment is 300r / min-1200r / min; the stirring temperature of the stirring treatment is 0℃-45℃; the stirring time of the stirring treatment is 1h-24h. In some specific embodiments, the stirring speed of the stirring treatment can be, for example, 300r / min, 400r / min, 500r / min, 600r / min, 800r / min, 1000r / min, 1200r / min; the stirring temperature of the stirring treatment can be, for example, 0℃, 5℃, 10℃, 15℃, 20℃, 25℃, 30℃, 35℃, 40℃, 45℃; the stirring time of the stirring treatment can be, for example, 1h, 2h, 4h, 5h, 6h, 8h, 10h, 12h, 14h, 15h, 16h, 18h, 20h, 22h, 24h. By controlling the relevant parameters of the stirring treatment within an appropriate range, the metallic lithium can be further fully contacted with the electrolyte, so that the surface of the metallic lithium can be fully passivated, ensuring that a passivation layer is formed on the surface of the metallic lithium, thereby reducing the chemical activity of the modified alkali metal particles, improving the stability of the reference electrode and extending its service life.

[0056] In the implementation manner of the present application, the reaction environment of step S101 is an inert gas atmosphere, including but not limited to an argon atmosphere in some specific embodiments.

[0057] In step S102, the pressure of the pressing compound is 1t-10t, the temperature is 22°C-28°C, and the time is 1s-5s. In some specific embodiments, the pressure of the pressing compound can be, for example, 1t, 2t, 4t, 5t, 6t, 8t, 10t; the temperature of the pressing compound can be, for example, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C; and the time of the pressing compound is 1s, 2s, 3s, 4s, 5s.

[0058] In the embodiment of the present application, before step S102, the non-woven fabric is also included in the modification of coating the non-woven fabric with a conductive polymer. The method of coating the conductive polymer on the surface of the non-woven fabric can be, for example: placing the non-woven fabric in a conductive polymer solution for a first immersion, taking it out and placing it at room temperature for a period of time, and then placing the wet non-woven fabric in an ethanol solution for a second immersion, and finally obtaining a non-woven fabric coated with a conductive polymer.

[0059] In some embodiments of the present application, the conductive polymer includes but is not limited to polyaniline, polypyrrole, and polyacetylene. In some embodiments of the present application, the mass percentage of the conductive polymer in the conductive polymer solution is 5%-25%. In some specific embodiments, the mass percentage of the conductive polymer in the conductive polymer solution can be, for example, 5%, 10%, 15%, 20%, and 25%. In some embodiments of the present application, the solvent of the conductive polymer solution is, but is not limited to, tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, and chloroform. In some embodiments of the present application, the temperature for dissolving the conductive polymer when preparing the conductive polymer solution is 60°C-80°C. In some specific embodiments, the temperature for dissolving the conductive polymer when preparing the conductive polymer solution can be, for example, 60°C, 65°C, 70°C, 75°C, and 80°C.

[0060] In some embodiments of the present application, the first immersion time is 0.5h-6h, specifically, for example, 1h, 2h, 3h, 4h, 5h, 6h. In some embodiments of the present application, the second immersion time is 0.5h-6h, specifically, for example, 1h, 2h, 3h, 4h, 5h, 6h.

[0061] In the embodiment of the present application, an ethanol solution is selected for the second immersion, because the conductive polymer is insoluble in the ethanol solution and will precipitate and adhere to the non-woven fabric, and the solvents of the conductive polymer solution such as tetrahydrofuran, N,N-dimethylformamide, dimethyl sulfoxide, chloroform, etc. will diffuse into the high concentration ethanol solution, promote the phase transfer process of the conductive polymer, and finally obtain a non-woven fabric coated with a porous conductive polymer.

[0062] The reference electrode preparation method provided in the present application is novel, has a simple preparation process, and is conducive to industrial production. The reference electrode prepared by the method has both excellent monitoring accuracy and a long service life.

[0063] The present application also provides a battery, which includes a positive electrode, a diaphragm, a reference electrode, a diaphragm, a negative electrode, and an electrolyte located between the positive electrode and the negative electrode, wherein the reference electrode includes the reference electrode provided above or the reference electrode prepared by the preparation method provided above. The reference electrode provided in the present application is arranged between the positive electrode and the negative electrode to accurately monitor the battery potential.

[0064] The present application also provides an electric device, which includes the battery provided in the foregoing text of the present application. The electric device may be, for example, an electric car, a mobile phone, a tablet computer, a laptop computer, a wearable device (a watch, a bracelet), a digital camera, etc.

[0065] The present application is further described below in multiple embodiments:

[0066] Example 1

[0067] (1) Under an argon atmosphere, 10 g of metallic lithium with a particle size D50 of 1 μm was added to 200 mL of an electrolyte, wherein the lithium salt was LiPF6 with a concentration of 1 mol / L, and the solvent was ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1:1, and after stirring at 600 r / min at 25°C for 12 h, the obtained product was dried at 25°C for 24 h to obtain modified alkali metal particles coated with a passivation layer, wherein the thickness of the passivation layer was 50 nm;

[0068] (2) Dissolve polyaniline in tetrahydrofuran at 80°C to obtain a polyaniline solution with a mass percentage of 10%, cut an initial PET non-woven fabric with a thickness of 2 μm and a length*width of 100 mm*5 mm, place it in the polyaniline solution and soak it for 6 hours, then place it on a clean glass, evaporate the free solution at room temperature, and then place the wet initial PET non-woven fabric in an ethanol solution and soak it for 2 hours to obtain a specific surface area of ​​1.2 m 2 / g of polyaniline coated modified non-woven fabric, the polyaniline coated modified non-woven fabric having a porous hole structure with a pore size range of 0.01μm-5μm, wherein the thickness of the polyaniline coating layer is 1μm, and the diameter of the non-woven fabric fiber matrix is ​​2.5μm;

[0069] (3) The polyaniline coated nonwoven fabric was placed in a pressing mold, and then 0.2 g of the prepared modified alkali metal particles were placed on the polyaniline coated modified nonwoven fabric for pressing and compounding. The pressing and compounding time was 2 s, the temperature was 25° C., and the pressure was 5 t to obtain a reference electrode.

[0070] Example 2

[0071] The difference from Example 1 is that the particle size D50 of the metallic lithium in step (1) is 0.05 μm.

[0072] Example 3

[0073] The difference from Example 1 is that the particle size D50 of the metallic lithium in step (1) is 10 μm.

[0074] Example 4

[0075] The difference from Example 1 is that the solvent of the electrolyte in step (1) is ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:3:1:3, and the thickness of the passivation layer is 80 nm.

[0076] Example 5

[0077] The difference from Example 1 is that in step (1), the lithium salt of the electrolyte is LiFSI with a concentration of 1 mol / L, and the thickness of the passivation layer is 1 nm.

[0078] Example 6

[0079] The difference from Example 1 is that in step (1), the concentration of lithium salt in the electrolyte is 1.2 mol / L, and the thickness of the passivation layer is 100 nm.

[0080] Example 7

[0081] The difference from Example 1 is that in step (2), the mass percentage of polyaniline in the polyaniline solution is 5%, and the specific surface area is 1.2 m 2 / g of polyaniline coated and modified non-woven fabric, wherein the thickness of the polyaniline coating layer is 0.1 μm, and the diameter of the non-woven fabric fiber matrix is ​​2.5 μm.

[0082] Example 8

[0083] The difference from Example 1 is that in step (2), the mass percentage of polyaniline in the polyaniline solution is 25%, and the specific surface area is 0.2 m 2 / g of polyaniline coated and modified non-woven fabric, wherein the thickness of the polyaniline coating layer is 2 μm, and the diameter of the non-woven fabric fiber matrix is ​​2.5 μm.

[0084] Example 9

[0085] The difference from Example 1 is that the amount of modified alkali metal particles added in step (3) is 0.4 g.

[0086] Example 10

[0087] The difference from Example 1 is that the amount of modified alkali metal particles added in step (3) is 0.8 g.

[0088] Embodiment 11

[0089] The difference from Example 1 is that in step (2), the conductive polymer is polypyrrole.

[0090] Comparative Example 1

[0091] (1) Dissolve polyaniline in tetrahydrofuran at 80°C to obtain a polyaniline solution with a mass percentage of 10%, cut an initial PET non-woven fabric with a thickness of 2 μm and a length*width of 100 mm*5 mm, place it in the polyaniline solution and soak it for 6 hours, then place it on a clean glass, evaporate the free solution at room temperature, and then place the wet initial PET non-woven fabric in an ethanol solution and soak it for 2 hours to obtain a specific surface area of ​​1.2 m 2 / g of polyaniline coated modified non-woven fabric, the polyaniline coated modified non-woven fabric having a porous hole structure with a pore size range of 0.01μm-5μm, wherein the thickness of the polyaniline coating layer is 1μm, and the diameter of the non-woven fabric fiber matrix is ​​2.5μm;

[0092] (2) The polyaniline-coated modified nonwoven fabric is placed in a pressing mold, and then 0.2 g of metallic lithium with a particle size D50 of 1 μm is placed on the polyaniline-coated modified nonwoven fabric for pressing and compounding. The pressing and compounding time is 2 s, the temperature is 25° C., and the pressure is 5 t to obtain a reference electrode.

[0093] Related parameter test

[0094] Specific surface area of ​​non-woven fabric: Take 0.5g of polyaniline-coated modified non-woven fabric for nitrogen adsorption and desorption test (instrument model: JW-BK300B) to test its BET specific surface area;

[0095] Thickness of the conductive polymer coating layer: The cross section of the polyaniline coated modified nonwoven fabric was tested using a scanning electron microscope (SEM) (instrument model: Zeiss Gemini300) to measure the coating thickness;

[0096] Diameter of nonwoven fiber matrix: SEM (instrument model: Zeiss Gemini 300) was used to test the cross section of the nonwoven fabric to measure the coating thickness;

[0097] Thickness of the passivation layer: The thickness of the passivation layer on the surface of lithium metal particles was measured using a transmission electron microscope (TEM) (instrument model: FEI Tecnai F20);

[0098] Compacted density: The mass of the reference electrode prepared in the embodiment and the comparative example was weighed using an analytical balance, the thickness of the reference electrode was measured using a micrometer, and the length and width of the reference electrode were measured using a ruler, and the area of ​​the reference electrode was calculated (the area of ​​the reference electrode = the length of the reference electrode * the width), and the compacted density of the reference electrode = the mass of the reference electrode / (the thickness of the reference electrode * the area of ​​the reference electrode). The results are shown in Table 1.

[0099] Specific surface area of ​​the reference electrode: The reference electrodes prepared in the examples and comparative examples were taken as samples, and the BET specific surface area was tested by N2 adsorption and desorption. The structures obtained by the test are shown in Table 1.

[0100] Porosity test:

[0101] The initial mass of the reference electrode prepared in the embodiment and the comparative example was weighed by an analytical balance and recorded as W0. The reference electrode was then placed in a glove box with an Ar atmosphere and immersed in PC (propylene carbonate, density ρ = 1.2 g / cm 3 ) After 2 hours, wipe the free liquid on the surface of the reference electrode with dust-free paper, weigh the mass with an analytical balance, record it as W1, and calculate the porosity using the formula: porosity = (W1-W0) / ρ*V (V is the volume of the reference electrode, that is, V = thickness of the reference electrode * area of ​​the reference electrode). The results are shown in Table 1.

[0102] Monitoring accuracy test:

[0103] A positive electrode active slurry is prepared by taking lithium iron phosphate, conductive carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and the slurry is coated on a positive electrode collector to obtain a positive electrode plate. The negative electrode plate is a metal lithium plate. 1 mol of LiPF6 is dissolved in 1 L of a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1:1 to obtain an electrolyte. A copper wire lithium-plated reference electrode and a reference electrode prepared in the embodiment and the comparison are added to the negative electrode side, and the reference electrode and the positive and negative electrode plates are separated by a diaphragm to assemble a CR2032 button battery.

[0104] The test was carried out using a constant current charge and discharge mode, with constant current charging at a current density of 0.1C to a cutoff of 3.65V, and constant current discharge at a current density of 0.1C to 2V after standing for 5 minutes. The potential monitoring difference between the reference electrode of the embodiment and the comparative example and the copper wire lithium-plated reference electrode is shown in Table 1.

[0105] The button was tested for cycling with a current of 0.5C and a voltage range of 3.65V-2.0V. The potential monitoring difference of the reference electrode of the embodiment and the comparative example before and after 200 cycles was measured. The results are shown in Table 1.

[0106] Table 1

[0107]

[0108] It can be seen from the data in Table 1 that compared with Comparative Example 1 in which the alkali metal particles are not coated with a passivation layer, the reference electrode obtained by coating the alkali metal particles with a passivation layer and loading them in a non-woven fabric in the embodiment of the present application has higher monitoring accuracy and longer service life.

[0109] The preferred embodiments are described in detail above, but the present invention is not limited to the above-mentioned specific implementation modes. Under the guidance of the present application, technicians in this field can also make various specific changes without departing from the scope of protection of the present application, which all fall within the scope of protection of the present invention.

Claims

1. A reference electrode, characterized in that The reference electrode comprises a non-woven fabric and modified alkali metal particles loaded on the non-woven fabric, wherein the modified alkali metal particles comprise an alkali metal core and a passivation layer coated on at least a portion of the surface of the alkali metal core.

2. The reference electrode according to claim 1, characterized in that The non-woven fabric has a porous hole structure, and at least part of the modified alkali metal particles are contained in the porous holes.

3. The reference electrode according to claim 2, characterized in that The pore size of the porous holes is 0.01 μm-5 μm.

4. The reference electrode according to any one of claims 1 to 3, characterized in that The nonwoven fabric comprises a plurality of nonwoven fabric fibers, at least some of which are interwoven with each other, and at least some of which comprise a nonwoven fabric matrix and a conductive polymer coating layer coated on the surface of the nonwoven fabric matrix.

5. The reference electrode according to claim 4, characterized in that The diameter of the non-woven fabric fiber matrix is ​​0.5 μm-5 μm; the thickness of the conductive polymer coating layer is 0.1 μm-2 μm.

6. The reference electrode according to claim 4 or 5, characterized in that The specific surface area of ​​the nonwoven fabric is 0.5 m 2 / g-1.6m 2 / g.

7. The reference electrode according to any one of claims 4 to 6, characterized in that The material in the conductive polymer coating layer includes at least one of polyaniline, polypyrrole and polyacetylene.

8. The reference electrode according to any one of claims 1 to 7, characterized in that The particle size D50 of the alkali metal core is 0.05 μm-10 μm.

9. The reference electrode according to any one of claims 1 to 8, characterized in that The alkali metal core is metallic lithium.

10. The reference electrode according to any one of claims 1 to 9, characterized in that The thickness of the passivation layer is 1 nm-100 nm.

11. The reference electrode according to any one of claims 1 to 10, characterized in that The passivation layer is a SEI film coating layer, and the SEI film coating layer includes an inorganic lithium salt; the inorganic lithium salt includes at least one of LiF, Li2SO3, Li2SO4, LiN, Li3PO4, Li2CO3, Li2O, Li2O2, LiPF and LiPOF.

12. The reference electrode according to any one of claims 1 to 11, characterized in that The mass percentage of the modified alkali metal particles in the reference electrode is 10%-80%.

13. The reference electrode according to any one of claims 1 to 12, characterized in that: The thickness of the reference electrode is 1 μm-20 μm; the specific surface area of ​​the reference electrode is 0.6 m 2 / g-1.8m 2 / g; the porosity of the reference electrode is 20%-60%; the compaction density of the reference electrode is 1.5g / cm 3 -2.8g / cm 3 .

14. A method for preparing a reference electrode according to any one of claims 1 to 13, characterized in that: include: placing alkali metal particles in a passivation solution to obtain modified alkali metal particles; The modified alkali metal particles are pressed and compounded with non-woven fabric to obtain a reference electrode.

15. The method for preparing a reference electrode according to claim 14, characterized in that: The passivation solution includes a lithium salt and a solvent; the lithium salt includes at least one of LiPF6, LiClO4, LiFSI and LiTFSI; the solvent includes a carbonate solvent, and the carbonate solvent includes at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate.

16. The method for preparing a reference electrode according to claim 14 or 15, characterized in that: The method also includes coating and modifying the non-woven fabric with a conductive polymer before the pressing and compounding; the polymer includes at least one of polyaniline, polypyrrole and polyacetylene.

17. A battery, characterized in that: The battery comprises a positive electrode, a separator, a reference electrode, a separator, a negative electrode, and an electrolyte located between the positive electrode and the negative electrode, wherein the reference electrode comprises the reference electrode as described in any one of claims 1 to 13 or a reference electrode prepared by the preparation method as described in any one of claims 14 to 16.

18. An electrical equipment, characterized in that: The electric device comprises the battery as claimed in claim 17.

Citation Information

Patent Citations

  • Infiltration preparation method for lithium ion battery with reference electrode

    CN108107092A

  • Preparation method of lithium metal reference electrode and lithium metal reference electrode

    CN112563459A

  • Thin film reference electrode and preparation method thereof

    CN113514520A

  • Porous reference electrode, preparation method of porous reference electrode, battery and preparation method of battery

    CN114527178A

  • Lithium ion battery and preparation method thereof

    CN115548496A